Possible Effects of Religious Education in Prisons (Academic Journal of Internal Affairs, 2023)
Aim: The aim of the authors is to provide a comprehensive presentation of religious education in prisons, i.e. the impact of the prison mission on inmates. The tests point in the right direction. On the one hand, it covers strategies for coping with prison life, the attitude and values of prisoners, i.e. the internal change of the individual. On the other hand, the impact on the likelihood of recidivism among the prospects after prison life is examined.Methodology: By processing secondary sources, the authors process the data of the domestic and international literature, evaluating them and drawing conclusions.Findings: Prisoners who are regular participants in religious events prefer cooperative coping strategies much more than their peers who do not or hardly participate in such events. Differences can also be observed in the attitudes and value systems of individuals; several elements approach the direction of positive social practice. However, the effect of religious education on recidivism is far from clear. Research results are divided as to whether it has a significant effect.Value: One of the objectives of the penitentiary is to bring the convict back into society so that he becomes a useful member of it. One of the essential prerequisites for this is that prison harms affect the individual as little as possible. Religious education is a suitable tool for reducing negative effects. At the same time, becoming a relapser is influenced by countless external factors that can worsen favourable results. Therefore, this study also points out that the role of the prison mission, and with it the role of the churches, cannot end after release.
Keywords: religious education; prison mission; prison harms; becoming recidivist